Development and validation of a QuEChERS-LC-MS/MS method for determination of multiple mycotoxins in maize and sorghum from Botswana - Mbisana, Mesha; Rebagamang, Tshepho; Mogopodi, Dikabo; Chibua, Inonge (Frontiers in Fungal Biology, 2023)
Climatic conditions such as drought, high temperatures, and pre-harvest rainfalls promote the occurrence of mycotoxins in grains. Contamination of staple food sources such as maize and sorghum means that many populations are at risk of being poisoned by mycotoxins. Hence the need for sensitive methods for their simultaneous analysis. Herein, a quick, easy, cheap, effective, rugged, and safe liquid chromatography tandem mass spectrometry (QuEChERS-LC-MS/MS) method for the simultaneous determination of ten mycotoxins in maize and sorghum is presented. The QuEChERS extraction procedure was optimized to maximize extraction recovery and minimize matrix effects while using relatively small quantities of organic solvents and acids. This method was validated according to Commission Implementing Regulation (EU) 2021/808, Commission Regulation (EC) No 1881/2006, and Regulation (EC) no. 401/2006. The developed method met the specified requirements. Recoveries of 80.77% to 109.83% and CVs below 15% were obtained. The correlation coefficient values (R2) were all above 0.98, and low limits of quantification ranging from 0.53 to 89.28 µg/Kg were recorded. The method was applied to 10 maize and 10 sorghum samples collected from markets in Botswana. Half of the samples had detectable mycotoxins, Aflatoxins, Fumonisins, T2-toxin, HT2-toxin, and Zearalenone. Two maize samples had levels of aflatoxin B1 above the maximum permitted level (2.55, 4.07 µg/Kg). These findings point to the necessity of more stringent monitoring of mycotoxins, particularly AFB1 in maize, as well as the value of regular assessment using LC-MS/MS.